2012
DOI: 10.1515/znb-2012-0402
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Polyhalogenated Nitrobutadienes, Part 11: ipso-Formylation of 2-Chlorothiophenes under Vilsmeier-Haack Conditions

Abstract: The regioselective ipso-formylation of electron-rich, 3,4-push-pull-substituted 2-chlorothiophenes under Vilsmeier-Haack conditions was performed in good yields. The synthetic scope of this new reaction was explored using various halothiophenes, chloroanilines, and 1-methyl-3-chloroindole. In comparison with their structural C-H analogs the chlorinated thiophenes, anilines, and the indole proved to be less reactive toward electrophilic attack by chloromethyleniminium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The push-pull substituted thiophene 53 was efficiently accessible in 85% yield upon treatment of dithiolane 52 with sodium hydroxide using DMSO as solvent. The regioselective ipso-formylation of the 2-chloro-thiophene 53 under Vilsmeier-Haack conditions led to the carbaldehyde 54 (64% yield), according to [82].…”
Section: Thiophenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The push-pull substituted thiophene 53 was efficiently accessible in 85% yield upon treatment of dithiolane 52 with sodium hydroxide using DMSO as solvent. The regioselective ipso-formylation of the 2-chloro-thiophene 53 under Vilsmeier-Haack conditions led to the carbaldehyde 54 (64% yield), according to [82].…”
Section: Thiophenesmentioning
confidence: 99%
“…The next successive steps were performed with the most stable derivative 3-morpholino-4-nitro-5-(vinylthio)thiophene-2-carbaldehyde (55) [82]. Knoevenagel condensation of thiophene 55 with malononitrile in ethanol in the presence of a catalytic amount of sodium ethanolate gave the gem-dicyanovinylthiophene 56 in 68% yield [83].…”
Section: Thiophenesmentioning
confidence: 99%
“…For formylation of thiophene, Vilsmeier reaction is well known for the formulation of thiophene (Vogt et al, 2012;Su et al, 2010). Vilsmeier reaction has been performed which form comparatively weak electrophile (Scheme 1).…”
Section: Thf N-bulimentioning
confidence: 99%
“…Following a similar route, the Kaufmann group reported that the formylation process using the Vilsmeier reagent instead could also give the desired product, however, with a low yield of only 30% (Scheme 1b, condition B). 10 Jiang et al recently introduced a facile method that relies on the chlorination-oxidation of 2-indolylmethanols in the presence of 1,3-dichloro-5,5-dimethylhydantoin (DCDMH) (Scheme 1b). 11 However, this approach requires the preparation of alcohol as the starting material.…”
Section: Introductionmentioning
confidence: 99%